Least Squares Fitting with Cubic Splines - Khachatryan, Mane (Mathematical Problems of Computer Science, 2021)
In the paper cubic spline approximation of experimental data by least squares method is considered. An algorithm to construct a cubic spline with mixed-type boundary constraints is derived.